ESTABLISHMENT OF NEW ENTREPRENEURS IN THE FIELD OF LAND FISHERIES THE WATER SAVING - C. DYAH SULISTYANINGRUM INDRAWATI; DWI ARIES HIMAWANTO (CV KULTURA DIGITAL MEDIA, 2020)
Juwiring sub-district is one of the rices producing centers in Klaten. Most of his seats count on living as farmers, but things are disturbed by the fact that in recent years the harvest of rice in one of the largest rice producers in Klaten Regency can is said to be less successful due to attacks of leafhoppers and rat pests. This is impact on the lives of farmers and their families, especially in the three sub-districts the a.m. Capital issued to cultivate rice fields cannot be covered by for failing to harvest. The incident impacted farmers in the which is increasingly difficult to sustain his needs. Drape life in the agricultural sector, it is increasingly difficult because of many factors including the risk of crop failure and the high cost of production resulting in low income received per harvest. Therefore, the target group together with the team of advocates to solve the problem through efforts to training and establishment of new business groups in the field of land fisheries save water by invading fish enlargement ponds with a system of land fisheries with no running water.